Michael Addition to Nalidixic Acid and its Antitubercular Activity - RAMALINGAM, P.; BABURAO, CH.; GANAPATY, S. (Asian Journal of Chemistry, 2010)
α,β-Unsaturated site of nalidixic acid was subjected to Michael addition that afforded 14 new derivatives. All the compounds were characterized by spectral data and evaluated for its antitubercular activity against Mycobacterium tuberculosis H37Rν by Alamar blue assay.